P22phox C242T Single-Nucleotide Polymorphism Inhibits Inflammatory Oxidative Damage to Endothelial Cells and Vessels. Issue 24 (14th June 2016) - Meijles, Daniel N.; Fan, Lampson M.; Ghazaly, Maziah M.; Howlin, Brendan; Krönke, Martin; Brooks, Gavin; Li, Jian-Mei
Abstract : Background—: The NADPH oxidase, by generating reactive oxygen species, is involved in the pathophysiology of many cardiovascular diseases and represents a therapeutic target for the development of novel drugs. A single-nucleotide polymorphism, C242T of the p22 phox subunit of NADPH oxidase, has been reported to be negatively associated with coronary heart disease and may predict disease prevalence. However, the underlying mechanisms remain unknown. Methods and Results—: With the use of computer molecular modeling, we discovered that C242T single-nucleotide polymorphism causes significant structural changes in the extracellular loop of p22 phox and reduces its interaction stability with Nox2 subunit. Gene transfection of human pulmonary microvascular endothelial cells showed that C242T p22 phox significantly reduced Nox2 expression but had no significant effect on basal endothelial O2 .– production or the expression of Nox1 and Nox4. When cells were stimulated with tumor necrosis factor-α (or high glucose), C242T p22 phox significantly inhibited tumor necrosis factor-α–induced Nox2 maturation, O2 .– production, mitogen-activated protein kinases and nuclear factor κB activation, and inflammation (all P <0.05). These C242T effects were further confirmed using p22 phox short-hairpin RNA–engineered HeLa cells and Nox2 –/– coronary microvascular endothelial cells. Clinical significance was investigated by using saphenous vein segments from non–coronary heart disease subjects after phlebotomies. TT (C242T) allele was common (prevalence of ≈22%) and, in comparison with CC, veins bearing TT allele had significantly lower levels of Nox2 expression and O2 .– generation in response to high-glucose challenge. Conclusions—: C242T single-nucleotide polymorphism causes p22 phox structural changes that inhibit endothelial Nox2 activation and oxidative response to tumor necrosis factor-α or high-glucose stimulation. C242T single-nucleotide polymorphism may represent a natural protective mechanism against inflammatory cardiovascular diseases. Abstract : Supplemental Digital Content is available in the text.